Fertility challenges for women with sickle cell disease. Issue 10 (3rd October 2017) - Ghafuri, Djamila L.; Stimpson, Sarah-Jo; Day, Melissa E.; James, Andra; DeBaun, Michael R.; Sharma, Deva
ABSTRACT: Introduction : Sickle cell disease (SCD) represents one of the most common monogenic blood disorders worldwide, with an incidence of over 300, 000 newborns affected per year. Reproductive challenges for men and women with SCD have been previously reviewed; however, evidence-based strategies to prevent and manage infertility and increase fecundity are lacking in women with SCD, which is one of the most important factors for quality of life. Areas covered : This review article summarizes the known risk factors for infertility, low fecundity, and premature menopause related to SCD. Expert commentary : Women with SCD have unique risk factors that may impact their ability to conceive, including chronic inflammation, oxidative stress, transfusion-related hemochromatosis, and ovarian sickling, causing ischemia and reperfusion injury to the ovary. Contraception is strongly recommended while on hydroxyurea therapy during reproductive years and discontinuing hydroxyurea for family planning and during pregnancy based on teratogenicity in animal studies. Hematopoietic stem cell transplantation (HSCT), the only curative therapy, sometimes involves conditioning regimens containing alkylating agents and total body irradiation that contribute to infertility and premature ovarian failure. Prior to HSCT or gene therapy, we strongly recommend referral to a reproductive endocrinologist to discuss fertility preservation and surrogacy options for all women with SCD.